The improved giant magnetostrictive actuator oscillations via positive position feedback damper - Hany Bauomy; A. T. EL-Sayed; A. M. Salem; F. T. El-Bahrawy (AIMS Mathematics, 2023)
This article contemplates the demeanor of the giant magnetostrictive actuator (GMA) when a positive position feedback (PPF) damper is used to enable tight control over its vibration. The methodology followed here mathematically searches for the approximate solution for the motion equations of the GMA with the PPF damper, which has been accomplished by using one of the most famous perturbation methods. The multiple scale perturbation technique (MSPT) of the second-order approximation is our strategy to obtain the analytical results. The stability of the system has also been investigated and observed by implementing frequency response equations to close the concurrent primary and internal resonance cases. By utilizing Matlab and Maple programs, all numerical discussions have been accomplished and explained. The resulting influence on the amplitude due to changes in the parameters' values has been studied by the frequency response curves. Finally, a comparison between both the analytical and numerical solutions using time history and response curves is made. In addition to the comparison between our PPF damper's effect on the GMA, previous works are presented. To get our target in this article, we have mentioned some important applications utilized in the GMA system just to imagine the importance of controlling the GMA vibration.